Meminimalisir Stres Belajar Siswa Melalui Teknik Meditasi Hening - Arifin, Andi Agustan (Guidance and Counseling Study Program, Pattimura University, 2018)
Students in the process and learning activities should minimize the things that can interfere with the process of concentration of mind and attention in learning, whether the disturbance that comes from within and outside of students themselves. The silent meditation technique will affect the state of mind, and life. The state of mind also affects health in general, let alone be known that the students also range to stress due to lessons in school, resulting in low learning achievement. Therefore, students need a strong frame of mind and excellent health and a panacea to fight stress and that is a quiet meditation technique. The silent meditation technique will reduce stress accumulation, giving a positive effect on the state of mind and health in general.